2021
DOI: 10.1177/23742895211061822
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Remote Pathology Instruction in Student Performance and Course Evaluation

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disrupted undergraduate medical education, including preclinical class-based courses, by requiring social distancing and essentially eliminating in-person teaching. The aim of this study was to compare student performance and satisfaction before and after implementation of remote instruction in a first-year introductory pathology course. Assessments (3 quizzes, 1 practical exam, and 1 final) were compared between courses given before (January 2020) and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Our literature review revealed that the remote delivery of pathology courses worldwide was generally followed by highly positive student evaluations, as reported by several authors [3,5,9,10]. Notably, evaluation scores were often improved, compared to the previous years when traditional on-site delivery had taken place [5,9]. Medical students regarded the remote delivery of classes as flexible and less time-consuming, while they appreciated that teaching materials (e.g., session recordings and virtual slides) were available to access anytime and from anywhere [4,10].…”
Section: Advantages Of Virtual Pathology Education: Literature Reviewsupporting
confidence: 66%
See 4 more Smart Citations
“…Our literature review revealed that the remote delivery of pathology courses worldwide was generally followed by highly positive student evaluations, as reported by several authors [3,5,9,10]. Notably, evaluation scores were often improved, compared to the previous years when traditional on-site delivery had taken place [5,9]. Medical students regarded the remote delivery of classes as flexible and less time-consuming, while they appreciated that teaching materials (e.g., session recordings and virtual slides) were available to access anytime and from anywhere [4,10].…”
Section: Advantages Of Virtual Pathology Education: Literature Reviewsupporting
confidence: 66%
“…Our literature review revealed that the remote delivery of pathology courses worldwide was generally followed by highly positive student evaluations, as reported by several authors [3,5,9,10]. Notably, evaluation scores were often improved, compared to the previous years when traditional on-site delivery had taken place [5,9].…”
Section: Advantages Of Virtual Pathology Education: Literature Reviewsupporting
confidence: 66%
See 3 more Smart Citations